Study of glycemic gap in hyperglycemic emergencies of type 2 diabetes mellitus - Sivakumar, Periyasamy; Moonishaa, Thiyagarajan Manjuladevi; George, Neethu (International Journal of Research in Medical Sciences, 2018)
Background: Type 2 diabetes mellitus (T2DM) is associated with two serious hyperglycemic emergencies namely Diabetic ketoacidosis (DKA) and Hyperosmolar hyperglycemic state (HHS). The aim of the study was to determine the usefulness of glycemic gap in T2DM patients with DKA and HHS. Methods: T2DM cases above 20 years of age were included in this study. The study population was divided into three broad groups as T2DM without hyperglycemic emergencies, T2DM with DKA, T2DM with HHS, with 50 subjects in each group. Glycemic gap was calculated in the study population and compared between the three groups. The relationship between glycemic gap and the conventional indicators of severity in hyperglycemic emergencies of T2DM were determined. Results: Of the three study groups, T2DM cases with HHS presented with substantial alterations in the baseline biochemical parameters. The glycemic gap was also highly elevated in the HHS cases than the others. Glycemic gap showed significant correlation only with plasma osmolality of the HHS cases. Conclusions: Elevated glycemic gap indicating stress induced hyperglycemia (SIH) occur in hyperglycemic emergencies of T2DM, especially HHS.